2013
DOI: 10.1103/physrevstab.16.062002
|View full text |Cite
|
Sign up to set email alerts
|

Muon spin rotation studies of niobium for superconducting rf applications

Abstract: In this work we investigate superconducting properties of niobium samples via application of the muon spin rotation/relaxation (SR) technique. We employ for the first time the SR technique to study samples that are cut out from large and small grain 1.5 GHz radio frequency (rf) single cell niobium cavities. The rf test of these cavities was accompanied by full temperature mapping to characterize the rf losses in each of the samples. Results of the SR measurements show that standard cavity surface treatments li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
3
14
2
Order By: Relevance
“…The most apparent feature is the minimum observed at 50 K. In studies where the muon has been implanted in the bulk this feature has also been observed and was correlated to interstitial impurities [42]. A more recent study on cavity grade bulk niobium [43] has also found a minimum at 50 K. It has to be noted that in this study the variation of the hopping rate with temperature was much stronger than what is observed here. Also in [43] ν was obtained from zero field measurements only.…”
Section: Longitudinal Field Studies Of the Hipims Samplesupporting
confidence: 65%
“…The most apparent feature is the minimum observed at 50 K. In studies where the muon has been implanted in the bulk this feature has also been observed and was correlated to interstitial impurities [42]. A more recent study on cavity grade bulk niobium [43] has also found a minimum at 50 K. It has to be noted that in this study the variation of the hopping rate with temperature was much stronger than what is observed here. Also in [43] ν was obtained from zero field measurements only.…”
Section: Longitudinal Field Studies Of the Hipims Samplesupporting
confidence: 65%
“…Muon hopping rate of ν ∼ 0.7 MHz was determined at 2.5 K by Grasselino et al from ZF µSR experiments. 31 In zero field the muon experiences a spin depolarization due to nuclear magnetic fields which for a static case is described with the Kubo-Toyabe function: 28…”
Section: A Effect Of Muon Diffusion On Nb µSr Spectramentioning
confidence: 99%
“…The strong collision model was used in Ref. 31 for estimate of the hopping rate ν. Muon spin polarization within this model is described as follows: 18…”
Section: A Effect Of Muon Diffusion On Nb µSr Spectramentioning
confidence: 99%
“…For this purpose samples of ellipsoidal geometry have been produced. In the experiments reported in [4], the magnetic field was applied perpendicular to the sample surface, unlike in accelerating cavities. To resemble the field geometry of SRF cavities, a spectrometer that allows the application of fields of up to 300 mT parallel to the sample surface was built.…”
Section: Introductionmentioning
confidence: 99%